3^3+3^10÷3^8×3+3×3^7÷3^5+2×3^10÷(5×3^5+3^5)+93^3
Răspunsuri la întrebare
Răspuns de
2
3^3+3^10÷3^8×3+3×3^7÷3^5+2×3^10÷(5×3^5+3^5)+93^3 =
27+3^2×3+3^8:3^5+2×3^10: 3^5 × (5+1)+93^3 =
27 + 3^3+3^3+2 × 3^5 × 6 + 93^3 =
27 + 27 + 27 + 2 × 243×6 + 93^3 =
3 × 27 + 2916 + 804357 =
81 + 2916 + 804 357 =
807 354
_______
27+3^2×3+3^8:3^5+2×3^10: 3^5 × (5+1)+93^3 =
27 + 3^3+3^3+2 × 3^5 × 6 + 93^3 =
27 + 27 + 27 + 2 × 243×6 + 93^3 =
3 × 27 + 2916 + 804357 =
81 + 2916 + 804 357 =
807 354
_______
Alte întrebări interesante
Engleza,
8 ani în urmă
Limba română,
8 ani în urmă
Limba română,
8 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă